Applied research note: Determining the size and scope of USDA-exempted poultry processing in Pennsylvania - D.R. Boontarue; J.W. Boney (Journal of Applied Poultry Research, 2025)
Summary: To effectively educate small-scale poultry producers in Pennsylvania on their role in protecting commercial poultry industries, it is essential to first understand the size and scope of USDA-exempt poultry processing in the state. This study aimed to gather data from the state's 10 most poultry-dense regions to inform future extension programming. The counties identified with the highest meat bird densities included Lancaster, Lebanon, Berks, Snyder, Juniata, Union, Schuylkill, York, Perry, and Franklin. A seven-question anonymous survey was developed using Qualtrics to identify the location of growers, the nature of their processing operations, and the relevant exemption categories. Distribution of the survey was challenging, with limited responses from farmers' markets and processing facilities. However, one-on-one conversations and additional outreach via the Penn State Extension ListServ provided valuable insights. Most respondents raised birds outside the top 10 counties, with 72.6 % processing on-farm using personal equipment. Broilers were the most common species, and nearly half of the respondents raised multiple species. The ''Personal Use'' exemption category was most frequently selected (47.0 %), although many producers were unsure of their correct exemption category. Additionally, 59.7 % lacked a written biosecurity plan. These findings indicate a significant lack of awareness about USDA exemptions, likely due to limited enforcement and oversight. Given the dispersed nature of small-scale farms, future extension efforts should expand beyond poultry-dense counties and reassess their potential risks to the commercial industry.